OPTIMALISASI PENJADWALAN ULANG PADA PEMBANGUNAN CREW BOAT DENGAN METODE TIME COST TRADE OFF (TCTO) - Hamidah Zulfa Sarah; Fitri Hardiyanti; Yesica Novrita Devi (Proceeding Maritime Business Management Conference, 2023)
In project development, time and cost are very important factors, because the project can run according to plan. One of the reasons for conducting research on the crew boat construction project at one of the shipyards located in East Java. With a contract value of Rp57,203,300,000 and an agreed time of 250 days. But in the field there was a delay of 22 days, to overcome the delay an analysis was carried out using the Time Cost Trade Off method, and the application of crashing. By using the alternative of adding 3 hours of work (overtime) and alternative shifts. The results of this study show that applying the alternative of 3 working hours results in an optimum cost of Rp57,384,361,320 with an optimum time of 241 days. Meanwhile, the alternative of adding shifts resulted in an optimum cost of Rp59,051,420,070. with an optimum time of 205 days.